XII Mediterranean Conference on Medical and Biological Engineering and Computing 2010 c - Bamidis, Panagiotis D.; Pallikarakis, Nicolas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The MEDICON conferences are international events of high scientific standards with long lasting tradition held every third year in one of the Mediterranean countries under the auspices of the International Federation for Medical and Biological Engineering. This "MEDICON 2010(3y (Bconference proceedings present recent advances in practically every main topic of Biomedical Engineering. The volume provides communication and an exchange of ideas on Biomechanics, Bioinstrumentation, Medical Imaging, Medical Radiation Physics, Technology Assessment, Clinical Engineering, Rehabilitation Engineering, Medical Informatics, Biomaterials and Educational, Ethical and Professional Aspects.s
Biosignal Processing -- Medical Imaging -- Medical Devices and Instrumentation -- Biomedical Measurements and Modeling -- Web Based Medical Applications and Telemedicine -- e-Health -- BME Education -- Clinical Engineering.
Keywords: Engineering; Bioinformatics; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Biophysics and Biological Physics; Biomaterials; Computational Biology/Bioinformatics.